PHYSICAL LEARNING REVIEWED FROM THE ASPECTS OF MOTOR SKILLS, PARTICIPATION AND SOCIAL INTERACTION: A CASE STUDY REVIEW IN ELITE AND NON-ELITE KINDERGARTEN SCHOOLS - Riduan; Anggri Dwi Nata; Rahmat Sanusi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The problem in this study is the indication of differences in the implementation of physical education learning between schools with complete facilities and schools with limited facilities. The aim is to describe the quality of physical education learning at the kindergarten (TK) level from three main aspects: motor skills, participation, and social interaction, by comparing two types of schools: elite and non-elite kindergartens. This study uses a descriptive qualitative approach with a case study method. The research subjects included teachers and students from TK Cendekia (an elite school) and TK Negeri Pembina (a non-elite school) in Karimun Regency, Riau Islands. Data collection techniques were conducted through observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques, and their validity was tested through source and technique triangulation. The research results show that students in elite kindergartens have more developed motor skills, higher levels of participation, and better social interactions than students in non-elite kindergartens.